The methods of forming soft skills of university students: theoretical and practical aspects - Bella A. Uskova; Maria V. Fominykh (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper describes the theoretical and practical aspects of the methodology for the formation of students soft skills. Innovation processes are implemented today in almost all spheres of human activity. In particular, this applies to the field of education. As for professional education, the university should maintain interest in modern technologies, socio-economic changes in society, and the development of new trends and directions. Such processes include the formation of supra-professional skills, in other words, soft skills. They are not related to a particular profession, but are important for a career and advancement in it. The process of forming such skills can be implemented in English classes. In this regard, to create conditions conducive to the formation of soft skills, as well as to make the learning process more informative and memorable, the authors of the paper developed a set of tasks for the formation of soft skills competencies. Since the development of these skills is important for preparing for a future profession, the target audience is junior students. The purpose of this paper is a theoretical justification of the methodology for the formation of soft skills competencies. The practical significance of the research lies in the fact that the results can be used in the course of foreign languages teaching methodology.